Zimbabwe Electoral Commission election results relaying system - Ngwenya, Walter (Midlands State University, 2019)
This researcher undertook this project with a view to help improve the relaying of results by the Zimbabwe Electoral Commission by providing an alternative route of sending results to the various command centres around the country. With this proposed system the commission will be able to swiftly collate and aggregate results much faster and precise. Also in line with the United Nations Environment Programme (UNEP) Green Economy Initiative, Zimbabwe can help reduce its carbon footprint through adopting such technologies. The aim of the research was to design an electronic results relaying system based upon the electoral process adopted in Zimbabwe by the Electoral Commission. The system is meant to complement the fax system of transmitting results and the Excel based aggregation template system used in the current setup. The main objective of system development was to facilitate the transmission of election results from the various polling stations throughout the country to the national command Centre through a network based system and also an SMS based platform. A lot of emphasis was put on ensuring the system is temper proof and very secure through the use of various security techniques like mac addressing transactions and security camera snapshots. Positive results were obtained through the feasibility study carried out which indicated a greater benefit of carrying out the research. For requirements gathering the researcher made use of focus groups and one to one interviews with some of the ZEC staff. The developed system underwent various tests to ensure that its use would not compromise results transmission during an election.”